ChemInform Abstract: Cobalt‐Catalyzed, Aminoquinoline‐Directed C(sp2)—H Bond Alkenylation by Alkynes. Issue 10 (March 2015) - Grigorjeva, Liene; Daugulis, Olafs
Abstract The optimized procedure comprises air‐oxygen as terminal oxidant and Mn(O‐Ac)2 as co‐catalyst to produce isoquinoline scaffolds which are of interest in pharmaceutical and natural product syntheses.